2019
DOI: 10.1021/acsomega.9b01013
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Characteristics and Kinetics of Waste Camellia oleifera Shells by TG–GC/MS

Abstract: There is a large amount of Camellia oleifera shells generated as a waste product from industrial processes. Therefore, the high-value utilization of C. oleifera shells is a hotspot of current research. The thermal characteristics and kinetics of waste Camellia shells (WCOSs) were analyzed by thermogravimetry with gas chromatography–mass spectrometry (TG–GC/MS). The thermal behavior of WCOSs was studied at 10, 20, 40, and 60 °C/min, and the distributed activation en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…In addition, the weight loss of MIPW near 380 °C also includes the dehydration of silane alcohol groups in amorphous silica in MIPW, which changes the structure of silicon dioxide and makes the modified silica particles more prone to water loss at 500 °C to 600 °C, forming a more obvious weight loss peak [12]. Compared with MIPW, the DTG curve of COS has more obvious weight loss peaks around 250, 300 and 360 • C, a result similar to the data of Yang et al (10 • C/min) [13].…”
Section: Thermogravimetric Analysis Of Raw Materialssupporting
confidence: 78%
“…In addition, the weight loss of MIPW near 380 °C also includes the dehydration of silane alcohol groups in amorphous silica in MIPW, which changes the structure of silicon dioxide and makes the modified silica particles more prone to water loss at 500 °C to 600 °C, forming a more obvious weight loss peak [12]. Compared with MIPW, the DTG curve of COS has more obvious weight loss peaks around 250, 300 and 360 • C, a result similar to the data of Yang et al (10 • C/min) [13].…”
Section: Thermogravimetric Analysis Of Raw Materialssupporting
confidence: 78%
“…The molecular model of alcohol O–H and phenol O–H mainly uses the actual extracts existing in coals. According to the literature, 1-undecanol, 2-methyl-3-biphenylmethanol, 2-undecanol, 1,2,3,4-tetrahydro-4-methylphenanthrene-1-ol, 2,4-dimethyl-2-pentanol, phenol, 2-naphthol, 2-hydroxyanthracene, pyren-10-ol, 1,2-benzopyrene-4-ol, and 2,4-di- tert -butylphenol are selected.…”
Section: Methodsmentioning
confidence: 99%
“…Herein, we choose the fruit shell of Camellia oleifera Abel (SCOA) as a potential cellulose source and develop a process to produce two distinct types of CNCs simultaneously. As an agricultural waste, SCOA is produced in millions of tons every year but mostly burnt. , To produce CNCs from SCOA is therefore of great economic and environmental significance. It was reported that the morphology of SCOA is quite different from wood, and the composition analysis shows that SCOA contains significantly less cellulose but proportionally more lignin and hemicellulose than wood .…”
Section: Introductionmentioning
confidence: 99%